Development and Evaluation of a Digital Pop-Up Book on the Concept of Force for Fourth-Grade Science - Dini Hikmatul Fauziyah; Petra Kristi Mulyani (Jurnal Penelitian Pendidikan IPA, 2024)
Preliminary research, through observations, questionnaires, and interviews, showed problems in fourth-grade science learning media about force. This research aimed to develop a digital pop-up book on the concept of force This research used the research and development (RnD) method. The stages of the research were finding potential problems, data collection, product design, design validation, design improvements, product test, product revision, usage test, product revision, and mass production. Media experts validated the pop-up book and assessed it in a category of qualified with a score of 89.50%, meaning that the media emphasized information accordingly to the target; the choice of font and size was correct; the media was attractive, easy to use, made it easier for students to understand the material, and made it easier for teachers to deliver the lesson. The content expert validated the content on force and assessed the accuracy of the content in the category of very suitable with a score of 91.25%, which means that the material was presented coherently, encouraged students’ curiosity, was appropriate to support the lesson, activating students, increased students’ knowledge, had clear visuals and text, had concise and clear language, and delivered suitable language level. The effectiveness of digital pop-up books in improving students’ understanding of the material was shown in the t-test result (13.513) and an average increase (N-gain) of pretest and post-test data of 0.55 with medium criteria. Participants’ questionnaire showed their opinions on the excellent quality of digital pop-up books. This research indicated that digital pop-up books on the concept of force met the media and content qualification criteria, which motivated and helped the students comprehend the information.